2017
DOI: 10.3390/ijms18040711
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Exosomal Cardioprotective miRNAs Mitigates Hypoxia-Induced H9c2 Cells Apoptosis

Abstract: Recent evidence suggests that hypoxia caused by acute myocardial infarction can induce cardiomyocyte apoptosis. Exosomes are signalling mediators that contribute to intercellular communication by transporting cytosolic components including miRNAs, mRNAs, and proteins. However, the systemic regulation and function of exosomal miRNAs in hypoxic cardiomyocytes are currently not well understood. Here, we used small RNA sequencing to investigate the effects of hypoxia stress on miRNAome of rat cardiomyoblast cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…Zhang et al reported that exosomes derived from H9C2 cells carry certain cardioprotective miRNAs, which repress hypoxia-induced apoptosis. Among the hypoxia-induced exosomal miRNAs, miR-152-3p and let-7i-5p exert an anti-apoptotic function by targeting autophagy related 12 and Fas ligand, respectively ( 26 ). Cui et al confirmed that adipose-derived mesenchymal stem cell exosomes protect the ischemic myocardium from ischemia/reperfusion injury via activation of the Wnt/β-catenin signal pathway ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that exosomes derived from H9C2 cells carry certain cardioprotective miRNAs, which repress hypoxia-induced apoptosis. Among the hypoxia-induced exosomal miRNAs, miR-152-3p and let-7i-5p exert an anti-apoptotic function by targeting autophagy related 12 and Fas ligand, respectively ( 26 ). Cui et al confirmed that adipose-derived mesenchymal stem cell exosomes protect the ischemic myocardium from ischemia/reperfusion injury via activation of the Wnt/β-catenin signal pathway ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult cardiac myocytes treated with physiological concentrations of ethanol, for example, secreted more EVs [43]. Others demonstrated that stimulation with hypoxia for 48 h resulted in an elevated EV concentration but also with a higher rate of apoptosis probably due to the abiding absence of oxygen [44]. In addition, starvation of H9c2 cells also increased the release of EVs [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, regarding exogenous cel-miR-39 as free miRNAs in serum, we concluded that ExoQuick co-isolates a small proportion of free miRNAs while UC hardly precipitates any free miRNAs. Further, we found that incubation at 37℃ for 1 h can decrease the proportion of free miRNAs in exosome pellets and exosomal miRNAs like miR-126 and miR-152 [11][12][13]18] also decreased when RNase A was used. In conclusion, our findings provide essential information on the details of serum exosome isolation methods for further studies on exosomal miRNAs.…”
mentioning
confidence: 84%
“…Recently, an increasing number of extracellular miRNAs have been detected in exosomes isolated from biological fluids and cell culture media [4]. Moreover, some exosomal miRNAs have been shown to regulate disease development and reported as biomarkers of different types of cancers, cardiovascular disease and brain injury [11][12][13]. In addition to exosomal miRNAs, there are still some circulating miRNAs free in the serum [14].…”
mentioning
confidence: 99%